2006
DOI: 10.1111/j.1399-6576.2006.00955.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of propofol on P‐selectin expression and nitric oxide production in re‐oxygenated human umbilical vein endothelial cells

Abstract: This is the first study to demonstrate an effect of propofol upon endothelial P-selectin expression. Such an effect may be important in situations of reperfusion injury such as cardiac transplantation and coronary artery bypass surgery. We conclude that propofol attenuates re-oxygenation-induced endothelial inflammation in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Thus, exposure of macrophages to propofol has been shown to significantly inhibit lipopolysaccharide-induced nitric oxide synthesis (Chen et al, 2005). Propofol also decreases endothelial nitric oxide production in reoxygenated human umbilical vein endothelial cells (Corcoran et al, 2006), and ameliorates overproduction of nitric oxide in rats with cecal ligation and puncture (Yu et al, 2006). Our data indicate that in animals with halothane-induced liver injury, propofol inhibits iNOS overexpression induced by the volatile anesthetic, supporting this anti-inflammatory propertie of propofol.…”
Section: Discussionsupporting
confidence: 51%
“…Thus, exposure of macrophages to propofol has been shown to significantly inhibit lipopolysaccharide-induced nitric oxide synthesis (Chen et al, 2005). Propofol also decreases endothelial nitric oxide production in reoxygenated human umbilical vein endothelial cells (Corcoran et al, 2006), and ameliorates overproduction of nitric oxide in rats with cecal ligation and puncture (Yu et al, 2006). Our data indicate that in animals with halothane-induced liver injury, propofol inhibits iNOS overexpression induced by the volatile anesthetic, supporting this anti-inflammatory propertie of propofol.…”
Section: Discussionsupporting
confidence: 51%
“…As mentioned in the Introduction, measurements of NO end products in ECs exposed to chronic hypoxia have suggested either increased (7,25,58,59), decreased (28,53), or no alterations (10) in nitrite and nitrate levels. Differences in the EC type and duration of hypoxic exposure explain some of these different findings.…”
Section: Discussionmentioning
confidence: 97%
“…Measurements of the direct effect of hypoxia on ECs in culture, however, also revealed contrasting effects of chronic hypoxia: hypoxia was found to increase the formation of NO end products in cultured coronary ECs (7,25,44,59), whereas they were decreased in bovine aortic and pulmonary ECs and human umbilical vein ECs (HUVECs) (28,57); others reported no change in HUVECs (10). Measurments of the conversion of L-arginine to L-citrulline suggested that endothelial NOS (eNOS) activity decreases in bovine and human ECs exposed to chronic hypoxia (3,50).…”
mentioning
confidence: 91%
“…Although there are many elements of the immune system that work in concert to combat a septic insult, neutrophils are known to be essential first responders during sepsis (13). This seemingly simple event, neutrophil recruitment, occurs via a sophisticated process of cytokine cascades, cell‐to‐cell communication and the expression of redundant chemokines, that collectively aids in the delivery of neutrophils to a restricted area of tissue injury (14).…”
Section: Discussionmentioning
confidence: 99%